The international debt problem: An analysis of the Brady plan - Michael Frenkel (Intereconomics, 1989)
Recently the American Treasury Secretary, Nicholas Brady, launched a new initiative in which he proposed reducing the developing countries' bank debt. What are the elements of the plan, and which countries would benefit? What problems does it entail? Can it bring about a decisive improvement in the international debt situation of the developing countries? The following two articles attempt to answer these questions.
Keywords: 330; Indebtedness